Florida Solid and Hazardous Waste Regulation Handbook: Resource Conservation and Recovery Act (RCRA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The Resource Conservation and Recovery Act (RCRA) manages all aspects of solid and hazardous wastes. RCRA has separate requirements for generators of wastes, transporters of wastes, and owner/operators of facilities for treatment, storage, or disposal of hazardous waste. The requirements of RCRA include: permitting by EPA and exhaustive recordkeeping. The requirements are intended to track the movement and handling of the waste until it reaches final disposal. This is known as the cradle-to-grave approach to monitoring wastes. This is EDIS document FE444, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.